GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG DAGUSIBU OBAT DI KAMPUNG MARGOYUDAN KOTA SURAKARTA - Mursiany, Anita; Avrila, Nesya; Umboro, Recta Olivia (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
One of the most pressing needs of the community is medicine. People can buy medicines without a doctor's prescription or get them with a doctor's prescription. Until now, many people have purchased medicines independently without first consulting a medical professional. Due to ignorance and lack of information, this can result in cases of irrational drug use. Get, Use, Store, and Dispose (DAGUSIBU) medicine is a program designed to help families be aware of medicine. The purpose of this study is to determine how much knowledge the community in Margoyudan Village, Surakarta City, has about DAGUSIBU medicine. Purposive sampling was used in this study to select participants in a descriptive quantitative research design using questionnaires distributed to residents of Margoyudan Village. The percentage of correct answers was then analyzed and used to calculate the level of knowledge. Based on the results of the study, the general public's understanding of DAGUSIBU medicine in Margoyudan Village fell into three categories: good (68%), fair (23.9%), and poor (7.9%).